Soccer, society and motherhood: mothers, daughters and tackling gender norms - Pielichaty, H.; Velija, P. (Soccer & Society, 2026)
Traditionally soccer has been the preserve of men and boys and, in turn, for dads and sons to consume. The archaic, male-dominated environment of soccer has previously stifled girls` and women`s involvement in the sport as players and spectators. Soccer's elite sporting environment makes becoming a mother challenging and many athletes are forced to choose between athletic success or motherhood. The sport is undergoing rapid change, encouraged by government reviews, energized societal appeal and a generation of former female players now encouraging their own daughters into the game. This paper has important implications for policymakers, sports organizations, educators and researchers alike in terms of reimagining a space for mothers in soccer. As such, a call-to-action is made arguing for more research in this area from an interdisciplinary and intersectional perspective to promote gender equity on and off the pitch.